The potential moderating role of living in a conflict area on the link between classroom psychosocial stressors, perceived stress and change in anxiety symptoms in Israeli school children. Issue 4 (16th September 2022) - Behnsen, Pia; van Lier, Pol; Levavi, Kinneret; Marieke Buil, Joanne; Huizink, Anja; Koot, Susanne; Atzaba‐Poria, Naama
Abstract: Background: Perceived stress associated with relational victimization from peers and conflictual relations with the teacher have been linked with the development of anxiety symptoms in children. Living in conditions of ongoing stress from the broader environment has also been related to anxiety symptoms in children. In this study, we examined (a) the indirect effect between classroom psychosocial stressors (i.e., relational victimization and conflictual relationships with teachers), perceived stress and anxiety symptom development, and (b) whether this indirect effect was stronger for children living in a high threat region than for children living in a lower threat region. Methods: Children participating in the study attended elementary school either in a high threat of armed conflict region (15 s to hide in bomb shelter when alarm sounds, n  = 220) or in a lower threat of armed conflict region (60 s to hide in a bomb shelter when alarm sounds, n  = 188) in Israel. Children were first assessed on conflictual relationships with teachers and peers, subjectively perceived stress and anxiety in 2017 ( T 0 ; M age = 10.61 years, SD  = 0.78; 45% boys) and re‐assessed ( T 1 ) 1 year later, in 2018. Results: Perceived stress mediated the association between classroom psychosocial stressors and anxiety development. No moderation by threat‐region was found in this indirect effect. However, the association between perceived stress and anxiety development was only significant for children in the high threat region. Conclusion: Our study suggests that threat of war conflict amplifies the association between perceived stress and the development of anxiety symptoms. Abstract : Our study suggests that threat of war‐conflict plays a significant role in the relationship between perceived stress and anxiety symptoms and serves as an environmental risk factor for children's development of anxiety problems.